The Role of Environmental Performance in The Effect of Managerial Ownership, Independent Board of Commissioners, and Social Costs On Corporate Social Responsibility Disclosure - Sukhani, Nitya; Hanif, Hanif (AIBPM Publisher, 2023)
Concerning the social and environmental effects of monetary action, corporate social responsibility disclosure has become a phenomenon. Good corporate governance (GCG), which includes managerial ownership, company characteristics like the percentage of independent commissioners, extra costs incurred by the company, and media exposure like environmental performance are some of the variables that affect a company’s disclosure. This study’s ideas include the signaling theory. According to the signaling theory, businesses want to lessen the information gaps between them and their stakeholders by being transparent about the social activities they support and engage in. The manufacturing companies that took part in PROPER and are registered on IDX in 2019-2021 are the subject of this study. Purposive sampling was the technique that was employed. There are 30 companies that meet the requirements, and a total of 90 companies were obtained. The SPSS 26 program and Warp PLS 7.0 were used to perform the data analysis techniques, including the comparison of coefficients (pooling), outer model test and inner model test. This hypothetical result demonstrated that only environmental performance has a positive and significant effect on corporate social responsibility disclosure, proving the need for the government to enact regulations requiring companies to take part in PROPER.